Health Habits and Vitamin Supplementation of Young Female Students with a Family History of Cancer Diagnosis - Şahan, Özlem; Akarsu, Gökhan Doğukan; Akarsu, Rukiye Höbek; Atilla, Rabia (Progress in Nutrition, 2021)
Study Objectives: To examine the health habits and vitamin supplementation status of female students who were diagnosed with cancer in their family history. Methods: The research was conducted descriptively with female students studying at a public university in the Central Anatolia region of Turkey. In the study, 324 female students who accepted the study and were diagnosed with cancer in their families were included in the sample. Numeric and percentage statistics were used to analyze the data. Results: People with a family history of cancer need to have cancer screening and follow lifestyle recommendations because of the high risk of cancer. Conclusion: In this study, it was seen that cancer diagnosis in a relative can motivate to improve health behavior in individuals.